Seeds : time capsules of life - Kesseler, Rob.; Stuppy, Wolfgang; Charles, Prince of Wales, 1948-; Papadakis, Alexandra (San Rafael, California : Earth Aware Editions, 2012)
Photographer Rob Kesseler and seed morphologist Wolfgang Stuppy present a natural history of seeds illustrated with close up photographs and scanning electron micorgraphs.
"Published in collaboration with the Royal Botanic Gardens, Kew.
Includes bibliographical references and index.
Keywords: Seeds; Seeds -- Pictorial works